2018
DOI: 10.18240/ijo.2018.09.11
|View full text |Cite
|
Sign up to set email alerts
|

Lipid layer thickness and tear meniscus height measurements for the differential diagnosis of evaporative dry eye subtypes

Abstract: Obstructive MGD EDE and non-obstructive MGD EDE have significantly different clinical characteristics. Combining average LLT and TMH measurements enhanced their reliability for differentiating these two subtypes and provided guidance for offering more precise treatments for EDE subtypes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 27 publications
2
8
1
Order By: Relevance
“…In current study, the median value of LLT was 57 nm, which was thinner than the results in previous studies conducted by Jung et al [ 9 ] and Sang et al [ 15 ], in which the median LLT values in eyes with obstructive MGD were 79 nm and 75 nm, respectively. On the contrary, our results were similar to the study reported by Eom et al [ 7 ], who used the same instrument to measure the LLT in patients with obstructive MGD.…”
Section: Discussioncontrasting
confidence: 84%
See 1 more Smart Citation
“…In current study, the median value of LLT was 57 nm, which was thinner than the results in previous studies conducted by Jung et al [ 9 ] and Sang et al [ 15 ], in which the median LLT values in eyes with obstructive MGD were 79 nm and 75 nm, respectively. On the contrary, our results were similar to the study reported by Eom et al [ 7 ], who used the same instrument to measure the LLT in patients with obstructive MGD.…”
Section: Discussioncontrasting
confidence: 84%
“…A positive correlation between the LLT measurement and expressible MGs has been reported in several studies [ 7 , 8 , 15 , 17 ], indicating that the LLT assessments well reflect the quantitative changes of the meibum expression. Our data demonstrated that the LLT correlated well with MGE score in middle-aged and older groups, but not in young group.…”
Section: Discussionsupporting
confidence: 59%
“…The tear film is composed of a mucous layer, a watery layer, and a lipid layer. The lipid layer score is related to the meibomian gland function and correlates with dry eye symptoms [ 29 , 36 , 37 ]. Participants with a thicker lipid layer could be more likely to generate aerosols.…”
Section: Discussionmentioning
confidence: 99%
“…This result is in contrast to a previous study, which evaluated the same formulated eye drops and the conventional control therapy as evaluated in this study, and showed improvements in meibum quality and gland expressibility after 8 weeks of use. 13 This may be attributed to the lack of correlation between LLT and meibum quality scores, which was recently reported by Sang et al 28 While areas of tear break-up are often associated with thin lipid, it has been shown that this is not always the case, 29 which supports that the tear lipid is a poor barrier to evaporation if the composition and/or structure are defective. The lack of change in inferior LLT in this study, despite improvements to TER and TBUT with the formulated eye drops, seems to suggest that inferior LLT is not the primary driver in minimising TER.…”
Section: Clinical Sciencementioning
confidence: 92%